Cathodoluminescence studies of phosphors in a scanning electron microscope. (May 2015) - Harris, Paul; den Engelsen, Daniel; Ireland, Terry; Fern, George; Silver, Jack
Abstract: Cathodoluminescence studies are reported of phosphors in a field emission scanning electron microscope (FESEM). A number of phosphor materials have been studied and exhibited a pronounced comet-like structure at high scan rates, because the particle continued to emit light after the beam had moved onto subsequent pixels. Image analysis has been used to study the loss of brightness along the tail and hence to determine the decay time of the materials. This technique provides a simple and convenient way to study the decay times of individual particles.